FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL STATEMENT FRAUD DITINJAU DARI FRAUD TRIANGLE PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Sabat Adrian Kayoi; Fuad Fuad (Diponegoro Journal of Accounting, 2019)
This research aims to obtain empirical evidence about effectiveness of the fraud triangle are pressure, opportunity and rationalization in detecting financial statement fraud. The variables of the fraud triangle that used is a pressure with proxy financial stability (ACHANGE), external pressure (LEVERAGE), personal financial need (OSHIP), financial targets (ROA), opportunity with proxy ineffective monitoring and nature of industry (RECEIVABLE), and rationalization with proxy rationalization and foreign ownership. In this research to detecting financial statement fraud used a proxy earnings management with discretionary accruals as the dependen variabel. The population of this research is the banking companies listed in Indonesia stock exchange in 2015-2017. Total sample of this research is 58 manufacturing companies with three years observation. Data analysis was performed with the classical assumption and hypotesis testingusing linear regression. The result of this research indicates that the external pressure (LEVERAGE) and financial targets (ROA) influence the financial statement fraud. Meanwhile financial stability (ACHANGE), personal financial need (OSHIP), rationalization, ineffective monitoring, foreign ownership and nature of industry (RECEIVABLE) has no significan impact on financial statement fraud.